Seasonality and land cover characteristics drive aphid dynamics in an arid city. (September 2017) - Andrade, Riley; Bateman, Heather L.; Kang, Yun
Abstract: Urbanization of arid environments results in biotic communities that differ from the surrounding desert. The growth of cities has lowered biodiversity and increased abundance of generalist species, known as urbanophiles. However, the mechanisms by which specific organisms can dominate urban ecosystems remain unclear. Using an 11-year data set from the Central Arizona-Phoenix Long-Term Ecological Research program, we evaluated how aphids, an arthropod urbanophile, were affected by habitat type and seasonality in Phoenix, Arizona, USA. Twenty-five sites were selected in habitat types varying in land use and land cover characteristics. Aphids varied along a gradient of water availability and vegetation, rather than level of urbanization. Seasonal aphid abundance was the highest in the spring and lowest in the summer, a pattern that did not differ between habitat types. We developed a mathematical model parallel to our empirical study to explain how temperature may affect the temporal patterns. The analysis of our model demonstrated that although seasonal patterns were similar across habitats, slight shifts in microclimate can result in dramatic variation of population dynamics. We conclude that both land cover and climate have huge impacts on aphids and that urbanophiles are able to take advantage of favorable environmental conditions caused by urbanization. Highlights: We examine how urbanization affects aphids, a common arthropod urbanophile. We integrate a mathematical model to test the effects of temperature. Aphids respond to differences in water availability and resources between habitats. Urbanization does not affect the seasonal patterns of aphid abundance. Aphids are impacted by slight shifts in microclimate between habitat types.